Folded-plate structures with openings - analysis and optimization - Szybiński, Bogdan; Zieliński, Andrzej P.; Karaś, Marek (Computer Assisted Methods in Engineering and Science, 2023)
This paper is a continuation and development of the dissertation [1]. Complex folded-plate structures with holes are analyzed using the Trefftz-type finite elements, which appears very effective. The shape functions of these elements (Trefftz functions) fulfill respective differential equations. Then, a certain optimization algorithm is proposed, in which an optimized structure can have a large number of parameters used as optimization variables. Therefore, in particular stages of the proposed procedure, less important variable can be eliminated. The choice of the active variable set is based on investigation of sensitivity of the objective function and constraints on small changes of these variables.